Succession of bacteria and archaea involved in the nitrogen cycle of a seasonally stratified lake. Issue 1 (16th February 2023) - Diao, Muhe; Balkema, Cherel; Suárez-Muñoz, María; Huisman, Jef; Muyzer, Gerard
Abstract: Human-driven changes affect nutrient inputs, oxygen solubility, and the hydrodynamics of lakes, which affect biogeochemical cycles mediated by microbial communities. However, information on the succession of microbes involved in nitrogen cycling in seasonally stratified lakes is still incomplete. Here, we investigated the succession of nitrogen-transforming microorganisms in Lake Vechten  over a period of 19 months, combining 16S rRNA gene amplicon sequencing and quantification of functional genes. Ammonia-oxidizing archaea (AOA) and bacteria (AOB) and anammox bacteria were abundant in the sediment during winter, accompanied by nitrate in the water column. Nitrogen-fixing bacteria and denitrifying bacteria emerged in the water column in spring when nitrate was gradually depleted. Denitrifying bacteria containing nirS genes were exclusively present in the anoxic hypolimnion. During summer stratification, abundances of AOA, AOB, and anammox bacteria decreased sharply in the sediment, and ammonium accumulated in hypolimnion. After lake mixing during fall turnover, abundances of AOA, AOB, and anammox bacteria increased and ammonium was oxidized to nitrate. Hence, nitrogen-transforming microorganisms in Lake Vechten displayed a pronounced seasonal succession, which was strongly determined by the seasonal stratification pattern. These results imply that changes in stratification and vertical mixing induced by global warming are likely to alter the nitrogen cycle of seasonally stratified lakes. Abstract : Changes in stratification and mixing events impact on the nitrogen cycle of seasonally stratified lakes.